Penanaman Nilai-Nilai Islam pada Masyarakat di Dusun Rebile Desa Tanak Awu Kabupaten Lombok Tengah - Indana, Nurul; Musthofa, Ali (JUPIN (Jurnal Pendidikan Islam Nusantara), 2025)
Purpose of the study was to describe the strategy of instilling Islamic values in the community in Rebile Hamlet, Tanak Awu Village, Central Lombok Regency. The research method used by researchers is a qualitative method with a qualitative descriptive design. Data collection techniques used interviews, observation, and documentation. The data validity test uses extension of participation, persistence of observation, triangulation, and using reference materials. Data analysis techniques use data condensation, data presentation, verification and conclusions. Research results: 1. The cultivation of Islamic values in Rebile Hamlet uses the strategy of (a) Exemplary, where religious figures model how to speak and use polite language, besides that, religious figures also model exemplary examples such as going to pray in congregation to the mosque or to the musholla. (b) Habituation, which is done in the rebile hamlet is to hold a recitation routine on Saturday afternoon and yasin tahlil every Friday night. The last strategy is (c) Advice, about the morals and morals of fellow residents of rebile hamlet, namely mutual respect, help and love. 2. The process of instilling Islamic values in rebile hamlet: (a) Moral Knowing, namely Religious Leaders provide motivation and opportunities to ask residents about Islamic values. (b) Moral Loving/Feeling, namely Religious Leaders create a social environment that supports religious values such as supporting religious practices. (c) Moral Doing/Acting, namely residents of rebile hamlet who actively participate in religious activities and share food with neighbors.